A new species of the Choroterpes Eaton, 1881 subgenus Monophyllus Kluge, 2012 and a new record of the subgenus Choroterpes, s.s. (Ephemeroptera: Leptophlebiidae) from southern Western Ghats, India - Selvakumar, C.; Janarthanan, S.; Sivaramakrishnan, K. G. (Zootaxa, 2015)
A new species of Choroterpes (Monophyllus) is described based on larvae collected from rivers of Karnataka part of the Western Ghats. Choroterpes (Monophyllus) nandini n. sp. can be distinguished from the only other species viz., C. (Monophyllus) monophyllus by the following combination of characters: (i) median emargination of labrum moderately deep, without denticles; (ii) gills 2–7 without tracheation and (iii) abdominal segment 6 and 7 without colour pattern. Choroterpes (Choroterpes) petersi Tong and Dudgeon 2003 is newly recorded based on larval collections from the eastern and western regions of southern Western Ghats.